The development of two-week menu cycles for households with children allergic to wheat, soy, cow's milk and egg respectively - Matthee, Suzette (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc Consumer Sc)--Stellenbosch University, 2002.